Determinants of Performance of a Micro and Small Enterprises and their Role in Enhancing Local Economic Development: The Case Study Alibo Town, Oromia, Ethiopia - F. Shibeshi; F. Barasa (Journal of Applied Sciences and Environmental Management)
The objective of this paper was to investigate the determinants of micro and small enterprises performance and their role in enhancing local economic development in Alibo Town, Oromia, Ethiopia using Primary data collected from 281 respondents from questionnaire and interview. Data obtained shows that the majority (25.45%, 16.25%,6.45,3.42 and 12.50) of the MSE respondents in manufacturing, construction, urban agriculture, service and trade sub-sectors respectively respond that their saving amount had increased. While 1.42%, 2.15%,2.40%,1.75% and 2.01% respondents in manufacturing, construction, urban agriculture, service and trade sub-sectors respectively disagree to the increase in saving amount. However 0.75%,1.25%,2.25%,0.45%and 0.25% respondents in manufacturing, construction, urban agriculture, service and trade sub-sectors respectively did not response to increase in saving amount. Hence, results indicate working in MSEs helps to save more and saving condition of the respondents also improved through time.